Tingkat Kepuasan Masyarakat Atas Layanan Keagamaan Yang Diselenggarakan Direktorat Jenderal Bimbingan Masyarakat (Ditjen Bimas) Buddha Tahun Layanan 2018 - Dian Hafit Syaifullah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2019)
The religiousity services had been given by Ditjen Bimas Buddha since 2007. The problem faced was how to meet public service users who partially cultured the village with limited land, budget, and personnel owned. This study aims to find out: 1) the public satisfaction level of the religiousity services in the 2018 service year, 2) service elements that need to be prioritized for improvement in 2019. This research uses the survey method in accordance with Permenpan RB No. 14 of 2017. The study found that: 1) the public satisfaction level towards religiousity services of the Ditjen Bimas Buddha in the 2018 service year is 3.0045 categories "C" means "Poor" quality, 2) service elements that need to be prioritized for improvement in 2019 are the capacity of the service room and the completeness of facilities and infrastructure, the timeliness of delivery of service products, and the acceleration of service products delivery.